Description of Megistoleon thaumatopteryx sp. nov. with notes on the genus Megistoleon Navás (Neuroptera, Myrmeleontidae) - Badano, Davide (Zootaxa, 2013)
A new African species of antlion, Megistoleon thaumatopteryx sp. nov., is described from Mozambique. The poorly known genus Megistoleon Navás, 1931 and the only other species currently attributed to it, M. ritsemae (van der Weele, 1907) are redescribed in order to provide a better comparison with the new taxon. These myrmeleontids are easily distin-guishable by means of an exclusive set of characters besides a striking appearance.